Symptoms Improvement of Cerebral Venous Sinus Thrombosis: A Case Report - Komang Yunita Wiryaning Putri; Novan Krisno Adji; Muhammad Yudha Nugraha; Salsabila Maula Zalfa El Hamzah; Azham Purwandhono (Faculty of Medicine, University of Jember, 2022)
Cerebral venous sinus thrombosis (CVT) is a rare cause of stroke, a life-threatening disorder that occurs in approximately 0,5-1% of all stroke incidents. Various clinical presentations, risk factors, and neuroimaging findings of this disease may cause a delay in the early diagnosis and treatment of CVT. We discuss a case of a 34-year-old female who was admitted to the emergency room (ER) with the onset of a generalized tonic-clonic seizure with a progressive headache in the occipitotemporal region. Based on head CT, there was multiple hyperdense and cerebral venous infarction in the posterior left parietal lobe. D-dimer evaluation, there was an increasing level of D-dimer (>10.000 ng/mL). The patient was treated with the primary therapy heparin. After 15 days of being hospitalized, the patient was discharged without any sequelae. Keywords: CVT, heparin, stroke